The Effect of Giving Tens on Reducing Pain Levels in Low Back Pain Patients in Anugerah Sehat Physiotherapy Practice - Silitonga, Santo Damerius; Naibaho, Eka Nugraha V.; Nainggolan, Syahrul Handoko; Harahap, Ali Asman (CV. Devitara, 2024)
Physical activity requires energy to do it such as walking, going up and down stairs, lifting things, running. Pain can arise in various parts of the body and can be caused by many things, one of which is the working condition of lifting objects, this condition can cause excessive physical stress on the spinal cord so that it causes muscle spasms and makes the nerves squeezed and causes pain in the lower back. TENS is a physiotherapy modality that aims to reduce pain, by sending signals in the form of low-pressure electrical currents to nerves through the conductivity of electrodes attached to the skin area. The purpose of the study was to determine the effect of giving TENS on the reduction of pain levels in patients with low back pain in the practice of Physiotherapy Anugerah Sehat. The type of research used is a quantitative type of research, with the research design used is Quasi Experimental with a pre-test and post test one group approach. This research was carried out at the Anugerah Sehat Physiotherapy Practice in February 2024. The population in this study is 70 Low Back Pain patients.The sampling technique in this study uses a total sampling technique with the purposive sampling method, the number of samples in this study is 30 people. Pain scale measurements use the VAS scale. Bivariate analysis was used Paired Sample T Test analysis. The pain outcomes of patients with low back pain before the administration of the Tens modality were pain scale 4-6 (moderate pain) for 19 people (63.3%), pain scale 7-10 (severe pain) for 11 people (36.7%). The pain of patients with low back pain after the administration of the Tens modality was a pain scale of 1-3 (mild pain) as many as 21 people (70%), followed by respondents who felt a pain scale of 0 (mild pain) as many as 4 people (13.3%) and respondents who felt a pain scale of 4-6 (moderate pain) as many as 5 people (16.7%). There was an effect of TENS administration on the reduction of pain levels in patients with low back pain in the Anugerah Sehat physiotherapy practice with a significant value (2-tailed) 0.000<0.05.